Stress Distribution in Natural Tooth and Implant Supported Removable Partial Denture with Different Attachment Types: A Photoelastic Analysis - Majid Naser Khaki; Arash Shishehian (Islamic Dental Association of Iran, 2016)
Background and Aim: Different attachment designs have been developed to connect implant to natural teeth in partial dentures; however, adequate studies have not been performed to determine stress distribution patterns in these designs. The present study aimed to assess stress distribution patterns in natural tooth and implant supported removable partial denture with different attachment designs using photoelastic analysis. Materials and Methods: In this in vitro, experimental study, a photoelastic model of a partially edentulous mandible was fabricated and two Ankylosis implants were inserted at the site of first molar teeth bilaterally. Implants and teeth were connected by a partial denture and the acrylic base and implants were connected using ball and telescopic crown attachment types. Two crowns, one with resilient and the other one with rigid at-tachment were fabricated on the abutment teeth. Separate frameworks were designed and removable partial dentures were fabricated. Next, 100 N load was applied vertically to the area between implant and tooth. The pattern of stress distribution in implant in use of different implant-tooth attachment designs was studied by means of photoelastic method. Results: The lowest stress concentration was noted in use of resilient attachment while rigid attachment showed the highest level of stress concentration. Conclusion: Resilient attachment between implant and tooth created minimum stress concentration in implant; however, removable partial dentures were slightly instable in use of this attachment type. The decision to use different implant-tooth attachment types must be made based on clinical conditions.